2006
DOI: 10.1177/0731684406064997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Variables on the Quality of Compression Resin Transfer Molding

Abstract: Compression resin transfer molding (CRTM), combining resin transfer molding (RTM) and compression molding, have been developed to fabricate fiber reinforced plastic (FRP) components with large dimensions or high fiber volume content. Although a lot of literature on CRTM is available, relatively little useful technical information is present regarding the proper choice of molding conditions for component optimization. The objective of this research is to investigate the effects of process variables, including i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…As expected, a higher vacuum makes a better quality part, due to the less formed voids [1 -5] . A high mold cavity can reduce the resin flow resistance offered by the preform and be favorable for the resin penetration into the interstices of the preform [19] . However, it is not necessarily appropriate to use an excessively high mold cavity, since the C 1 is slightly less than C 2 in η .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…As expected, a higher vacuum makes a better quality part, due to the less formed voids [1 -5] . A high mold cavity can reduce the resin flow resistance offered by the preform and be favorable for the resin penetration into the interstices of the preform [19] . However, it is not necessarily appropriate to use an excessively high mold cavity, since the C 1 is slightly less than C 2 in η .…”
Section: Figurementioning
confidence: 99%
“…Many studies have been done to analyze the liquid flow, heat transfer and required clamping force [9 -17] . Investigations of the mechanical properties of the CRTM part are given in [18,19] . A new process, based on the separation and para llelization of the process steps " impregnation " and " forming and curing " , was also developed, to manufacture the parts with a high fiber volume fraction [20] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the mold is more expensive due to a sophisticated sealing system [68, 116,117]. Process optimization of the numerous process parameters has been done by means of modeling of all process stages [116,118,119].…”
Section: Compression Resin Transfer Molding (Crtm)mentioning
confidence: 99%
“…No major difference could be identified for the two sets of flexural strength for both RTM and CTM processes. Chang et al [15] investigated the effects of process variables, including injection pressure, mold opening distance, resin temperature, compression pressure, pre-heated mold temperature and cure temperature, on the quality of CRTM products by applying Taguchi's method. They reported that the compression pressure and the resin temperature are significant variables for improvements in the mechanical properties of the part.…”
Section: Introductionmentioning
confidence: 99%